Regulation of Rhcg, an ammonia transporter, by aldosterone in the kidney. Issue 2 (May 2021) - Eguchi, Koji; Izumi, Yuichiro; Yasuoka, Yukiko; Nakagawa, Terumasa; Ono, Makoto; Maruyama, Kosuke; Matsuo, Naomi; Hiramatsu, Akiko; Inoue, Hideki; Nakayama, Yushi; Nonoguchi, Hiroshi; Lee, Hyun-Wook; et al.
Abstract : Rhesus C glycoprotein (Rhcg), an ammonia transporter, is a key molecule in urinary acid excretion and is expressed mainly in the intercalated cells (ICs) of the renal collecting duct. In the present study we investigated the role of aldosterone in the regulation of Rhcg expression. In in vivo experiments using C57BL/6J mice, Western blot analysis showed that continuous subcutaneous administration of aldosterone increased the expression of Rhcg in membrane fraction of the kidney. Supplementation of potassium inhibited the effect of aldosterone on the Rhcg. Next, mice were subjected to adrenalectomy with or without administration of aldosterone, and then ad libitum 0.14 M NH4 Cl containing water was given. NH4 Cl load increased the expression of Rhcg in membrane fraction. Adrenalectomy decreased NH4 Cl-induced Rhcg expression, which was restored by administration of aldosterone. Immunohistochemical studies revealed that NH4 Cl load induced the localization of Rhcg at the apical membrane of ICs in the outer medullary collecting duct. Adrenalectomy decreased NH4 Cl-induced membrane localization of Rhcg, which was restored by administration of aldosterone. For in vitro experiments, IN-IC cells, an immortalized cell line stably expressing Flag-tagged Rhcg (Rhcg-Flag), were used. Western blot analysis showed that aldosterone increased the expression of Rhcg-Flag in membrane fraction, while the increase in extracellular potassium level inhibited the effect of aldosterone. Both spironolactone and Gӧ6983, a PKC inhibitor, inhibited the expression of Rhcg-Flag in the membrane fraction. These results suggest that aldosterone regulates the membrane expression of Rhcg through the mineralocorticoid receptor and PKC pathways, which is modulated by extracellular potassium level.